Sleep Quality and Related Factors Among Young People in Vietnam in 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current situation of sleep quality and identify some factors related to the sleep disturbances among young people in Vietnam in 2025.Subjects and methods: A cross-sectional descriptive study was conducted among 1,209 young individuals in Vietnam. Data were collected using an online questionnaire (Google Form), incorporating the Pittsburgh Sleep Quality Index (PSQI) to assess sleep quality. A global PSQI score >5 was used to define sleep disturbance. Data were analyzed using R version 4.3.2. The Chi-square (χ²) test and logistic regression models were employed to identify associated factors, with a statistical significance level set at p
Keywords: Pittsburgh Sleep Quality Index (PSQI), young people, sleep quality, Vietnam.